2018
DOI: 10.1002/mats.201800027
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbranched Polymers Formed Through Self‐Condensing Vinyl Polymerization in a Continuous Stirred‐Tank Reactor (CSTR): 1. Molecular Weight Distribution

Abstract: A new Monte Carlo simulation algorithm, based on the random sampling technique, is proposed for the self-condensing vinyl polymerization conducted in a continuous stirred-tank reactor. In order to highlight the most fundamental aspects of the reaction system, the kinetic rate constants are assumed to be constant, and the size and structure dependence is neglected. With this ideal model, the high molecular weight (MW) tail of the weight fraction distribution W(P) is shown to follow the power law, W(P) ∝ P −α . … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…To set the value of ξ corresponds to fixing the steady state conversion level, x A . For a CSTR, it was found that the weight-average molecular weight cannot reach the steady state for large t cases [8,9], and similar behavior was also reported for the SCVP [20,21] which is another route to synthesize HB polymers. The upper limit ξ-values above which the weight-average molecular weight cannot reach the steady state for a given reactivity ratio r was shown graphically in the earlier publication [9].…”
Section: Methodssupporting
confidence: 64%
“…To set the value of ξ corresponds to fixing the steady state conversion level, x A . For a CSTR, it was found that the weight-average molecular weight cannot reach the steady state for large t cases [8,9], and similar behavior was also reported for the SCVP [20,21] which is another route to synthesize HB polymers. The upper limit ξ-values above which the weight-average molecular weight cannot reach the steady state for a given reactivity ratio r was shown graphically in the earlier publication [9].…”
Section: Methodssupporting
confidence: 64%
“…For the present ideal polymerization systems, it was found that the weight-average molecular weight (MW) cannot reach the steady state for large residence time cases. [9,16] The critical ξ-value, ξ c above which the weight-average MW cannot reach the steady state for a given reactivity ratio r is shown in Figure 6. [9] The MC simulation was conducted mainly for ξ < ξ c .…”
Section: Methodsmentioning
confidence: 99%
“…[9,16] The critical ξ-value, ξ c above which the weight-average MW cannot reach the steady state for a given reactivity ratio r is shown in Figure 6. [9] The MC simulation was conducted mainly for ξ < ξ c . Figure 7 shows how the number of units incorporated into the largest cluster of tri-branched dendritic units, P LC changes with the degree of polymerization, P. In the case of a CSTR, P LC is larger for large polymers.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations